Squamous cell carcinoma in left flank due to saree: Largest reported case - Mandhane, Nisha; Shaikh, Tanveer Parvez; Ansari, Sharique; Deolekar, Sandesh; Karandikar, Sangram; Sreedharan, Lokesh; Ali, Sheena (International Journal of Research in Medical Sciences, 2017)
Saree is a female costume unique for Indian ladies. This includes a superficial cloth and a skirt underneath which is fastened securely to the waist by a cord. Persistent and long term wearing of this costume has resulted in waist dermatoses. Waist dermatoses theoretically may present with malignant transformation. Here we present a case of 60 year old female who presented with left flank ulcer following chronic irritation from saree, biopsy was taken and it showed squamous cell carcinoma (SCC). We decided to do wide excision with tension free suturing. Post operatively the patient followed up for 12 week and has shown to be disease free. This turns out to be the third case being reported and the largest ever to be reported in the literature.